Aulas-oficina de física moderna integrando TIC e demonstração experimental - João, Herbert Alexandre (2016)
The present work intends to produce and provide instructional material to high school teachers of physics, focusing on workshop methodology as a viable alternative to physics classes. It is proposed to equip teachers with innovative tools and context for the process of teaching-learning physics, based on the use of Information and Communication Technologies (ICT) and experimental practices. Detailed scripts were developed for the implementation of the methodology and offer of workshops in classrooms about Modern Physics (MP). From the literature it was observed that the workshops when developed with its own teachers, would make it possible to overcome deficits in their initial formation, including those regarding to the use of experimentation, technology, innovative methodologies and concepts of MP. Studies have demonstrated the real need to help teachers in the search for new alternatives for insertion of physics and its teaching in the social and technological reality of its students; As well as the effectiveness of instructional material in overcoming, even if timidly, some shortcomings with regard to pedagogical practice and the teaching of certain challenging content, in a contextualizing and motivating perspective.